KEBIJAKAN PENDIDIKAN ISLAM PADA ERA GLOBALISASI, PASAR BEBAS DAN REVOLUSI INDUSTRI 4.0 - Muhammad Nur asmawi (Scolae: Journal of Pedagogy, 2018)
This article examines Islamic education policies in the era of globalization, free markets and industrial revolution 4.0. A new era that emphasizes the pattern of digital economy, artificial intelligence, big data, robotic, and so on, or known as the disruptive innovation phenomenon. This paper seeks to reveal the shift in the function of contemporary education towards education as profit oriented. These social changes are addressed by the government with educational policies as public policies with their presence, among others: Kurikulum 2013, Kerangka Kualifikasi Nasional Indonesia (KKNI), e-learning, cyber University and so on to answer the challenges of the globalization era characterized by free markets and industrial revolutions 4.0.